The Emotionalization of Reflexivity - Holmes, Mary (Sociology (Oxford), 2010)
Reflexivity refers to the practices of altering one's life as a response to knowledge about one's circumstances. While theories of reflexivity have not entirely ignored emotions, attention to them has been insufficient These theories need emotionalizing and this article proposes that emotions have become central to a subjectivity and sociality that is relationally constructed. The emotionalization of reflexivity not only refers to a theoretical endeavour but is a phrase used to begin to explore whether individuals are increasingly drawing on emotions in assessing themselves and their lives. It is argued that dislocation from tradition produces a reflexivity that can be very dependent on comparing experiences and can move others to reflect and reorder their own relations to self and others. Thus, emotions are crucial to how the social is reproduced and to enduring within a complex social world.